Plastic biodegradation by in vitro environmental microorganisms and in vivo gut microorganisms of insects - Yang, Xian-Guang; Wen, Ping-Ping; Yang, Yi-Fan; Jia, Pan-Pan; Li, Wei-Guo; Pei, De-Sheng (Frontiers in Microbiology, 2023)
Traditional plastics, such as polyethylene (PE), polystyrene (PS), polypropylene (PP), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polyurethane (PUR), and other plastic polymers, are difficult to degrade and gradually accumulated in the environment to cause a serious environmental problem, which is urgently needed to develop novel treatments or control technology. The biodegradation of plastics causes great attention due to the advantages of green and safe characteristics. Microorganisms play a vital role in the biodegradation of plastics, including environmental microbes (in vitro) and gut microbes of insects (in vivo). Microbial degradation in environmental conditions in vitro is extremely slow for major plastics at degradation rates on basis of a month or even year time; but recent discoveries show the fast biodegradation of specific plastics, such as PS, PE, PUR, etc. Some invertebrates, especially insects, could be enhanced at rates on basis of hours; the biodegradation in insects is likely to gut microbial-dependent or synergetic bioreactions in animal digestive systems. This review comprehensively summarizes the latest 7 years (2016-2022) publications on plastic biodegradation by insects and microorganisms, elucidates the mechanism of plastic degradation in insects and environmental microbes, and highlights the cutting-edge perspectives for the potential applications of plastic biodegradation.